2003
DOI: 10.1067/mhn.2003.13
|View full text |Cite
|
Sign up to set email alerts
|

Task Performance in Stapedotomy: Comparison Between Surgeons of Different Experience Levels

Abstract: The observed differences in task performance may contribute to an understanding of maneuvers that increase the risk of inadequate prosthesis placement and cochlear trauma-factors likely responsible for variable hearing results with strapedotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 18 publications
3
16
0
2
Order By: Relevance
“…Previous studies showed that the role of haptic feedback could be different for experienced and inexperienced surgeons [2][10] [11]. Our results are promising in terms of clinical practice, since enhanced perception performs well in a variety of different conditions.…”
Section: Discussionsupporting
confidence: 66%
“…Previous studies showed that the role of haptic feedback could be different for experienced and inexperienced surgeons [2][10] [11]. Our results are promising in terms of clinical practice, since enhanced perception performs well in a variety of different conditions.…”
Section: Discussionsupporting
confidence: 66%
“…The success of the procedure is dependent on the surgeon's dexterity and experience [12]. Partial or complete restoration of conductive hearing loss is observed in up to 90% of cases [9].…”
Section: Rationalementioning
confidence: 99%
“…Reports have been written of incus and stapes footplate stimulators constructed using wardbased materials [12,13], but reports of objective performance from their use have not been published. In a temporal bone model of stapedotomy [14], experienced and novice surgeons were compared by their performance during fenestration, the degree of force applied to the footplate, prosthesis crimp quality and prosthesis mobility during crimping. Based on their results of experienced surgeons better targeting the fenestration, less prosthesis migration during crimping and that the most common cause of failed stapes surgery is a migrated prosthesis, these authors suggest that in teaching techniques for enhancing precision in stapedotomy, strategies for dampening natural tremor and optimal instrument trajectory should be emphasized.…”
Section: Trainingmentioning
confidence: 99%